(untitled) (UNWE Yearbook, 2022)
The Industrial Internet of Things (IIoT) is a new paradigm that fundamentally changes the current patterns and activities in industry. The new Digital revolution transforms all sectors of human activities and production. IIoT has numerous architectural, business, technological, social and consumer perspectives. This paper looks at some reference architectures, connectivity issues, business aspects and security topics of IIoT. Those domains are looked at with their most important subdomains into a framework that can allow an architect or end user to make a quantitative assessment of a IIoT. The proposed approach uses expert evaluation of the main domains and subdomains from a reference IIoT architecture, which are then used to obtain an overall IIoT assessment.